2019
DOI: 10.1111/cp.12161
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culture on cognitive appraisals: Implications for the development, maintenance, and treatment of posttraumatic stress disorder

Abstract: Objective: Cognitive appraisals have a central role in the development, maintenance, and treatment of posttraumatic stress disorder (PTSD). Accumulating cross-cultural psychology research has demonstrated that culture affects the way in which an individual cognitively appraises an everyday experience. However, to date, there is little empirical work considering the influence of culture on cognitive appraisals in PTSD and the implications for treatment. The objective of this review article was to consider how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 78 publications
3
38
0
Order By: Relevance
“…However, this evidence is derived predominately from Western, English-speaking patients, and largely ignores trauma survivors from other cultural groups [6]. Hence, most existing PTSD treatments are based on Western cultural norms, beliefs and values [6][7][8]. Consequently, culturally tailored PTSD interventions are scarce [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this evidence is derived predominately from Western, English-speaking patients, and largely ignores trauma survivors from other cultural groups [6]. Hence, most existing PTSD treatments are based on Western cultural norms, beliefs and values [6][7][8]. Consequently, culturally tailored PTSD interventions are scarce [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…family members) to assist in navigating social stressors. Moreover, cultural research has also demonstrated that variations in individualism–collectivism self-identity affect cognitive appraisals of general and threatening situations (Bernadi et al, 2019; Krieg and Xu, 2018; Mesquita et al, 2016), with mental health consequences (De Vaus et al, 2017; Jobson, 2009; Liddell and Jobson, 2016). Considering how psychological and cultural mechanisms influence the impact of settlement policies on refugees may therefore be important (Nickerson et al, 2015), as well as how cultural differences may shape post-traumatic psychological symptoms depending on contextual factors like the experience of PMLDs (Jayawickreme et al, 2012; Jobson, 2009; Liddell and Jobson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an extension of theoretical models is required, to help explain the development and maintenance of PTSD in a culturally-sensitive manner. Thus far, the existence of these models is rather limited (Bernardi, Engelbrecht, & Jobson, 2018;Hinton, Ojserkis, Jalal, Peou, & Hofmann, 2013;Maercker & Horn, 2013). In our working group, the socio-interpersonal model of PTSD was developed, which explicitly takes cultural aspects into account (Maercker & Hecker, 2016;Maercker & Horn, 2013).…”
Section: Modeling Of Culturally-specific Trauma Conceptsmentioning
confidence: 99%